Cs2CO3-Promoted C-3 Alkylation of 4-[(2,2-Difluoroethyl)amino]-5,5-disubstituted Furan-2(5H)-ones with Heteroarylmethyl Chlorides - Yu, Zhao; Xinlei, Liu; Weiwei, Wang; Rui, Geng; Wang, Mingan (Synthesis, 2018)
4-(2,2-Difluoroethylamino)-3-(heteroarylmethyl)-5,5-disubstituted furan-2(5H)-ones were regioselectively synthesized via C-3 alkylation of 4-(2,2-difluoroethylamino)-5,5-disubstituted furan-2(5H)-ones with heteroarylmethyl chlorides using Cs2CO3 as a base in 62–85% yields. Their structures were characterized by 1H and 13C NMR, HRMS (ESI), and X-ray diffraction. This C-alkylation selectivity was rationalized by bulky hindrance and electron-withdrawing effects.
Keywords: 5-spirocyclic furan-2(5H)-one; synthesis; regioselectivity; C-alkylation